O funcionamento do GPS e a matemática do ensino médio - Moraes, Marcelo Cardozo de (2015)
The main objective of this work is to make students understand the mathematical foundations for the operation of Global Positioning System (GPS). The research was done in a school in the state of São Paulo with students of the second year of high school and the analysis was done in a qualitative as well as quantitative manner. Two sheets of directed activities, were used so students were induced to understand what happens at the intersection of spherical surfaces and this was carried out in three stages. During the first activity, students reviewed the circles of intersection of ideas, both geometrically and algebraically. In the second activity, these ideas were enlarged to spheres. The operation of the GPS was exposed in the activity three using PowerPoint slides, so goal that students learned a little about the history of the GPS creation and its operation, and the central theorem of this work: "If four spherical surfaces intersect and their centers are not coplanar, then this intersection is a single point." The Didactic Engineering was the methodology used for the survey. The result indicates that although many students present difficulties during the activities, everyone understood the mathematical principles behind the GPS operation.